What and why: the current situation and future prospects of "ivy sign" in moyamoya disease - Jin Yu; Qian Du; Hui Xie; Jiayi Chen; Jincao Chen (SAGE Publishing, 2020)
"Ivy sign" is a special imaging manifestation of moyamoya disease (MMD), which shows continuous linear or punctate high intensity along the cortical sulci and subarachnoid space on magnetic resonance images. Ivy sign was reported to reflect the development of compensatory collaterals, and to be closely related to hemodynamic changes and clinical symptoms, and to indicate the postoperative prognosis, in MMD patients. It is a unique and critical marker for MMD. However, due to the lack of consistent criteria, such as definition, grading, and identification standards, ivy sign has not received much attention. We undertook a comprehensive literature search and summarized the current situation regarding ivy sign in MMD in terms of baseline characteristics, detection methods, definition, regional division and distribution patterns, grading criterions, incidence, related factors, the mechanism of ivy sign, and the effects of treatments. We also provided related concerns raised and future prospects relevant to studies about ivy sign in MMD.